Toward free trade in the Americas - Salazar X., José Manuel (Salazar Xirinachs); Robert, Maryse (Brookings Institution Press : Organization of American States, 2001)
Annotation In the past 15 years, the nations of the Western Hemisphere have staged a remarkable revolution -- in the way they trade with their neighbors. First, after decades of restrictive import policies, several countries began to liberalize their trade and investment regimes. Then, beginning a decade ago, numerous bilateral and sub-regional trade agreements were achieved, to serve as vital complements to domestic reforms and to foster trade flows among member countries. At the Second Summit of the Americas in 1998, negotiations among 34 democracies were launched to establish the Free Trade Area of the Americas (FTAA). This report takes stock of the remarkable progress to date in the development of free trade in the Western Hemisphere. It examines trade flows between countries in the same regional groupings and between members of different sub-regional arrangements. The report describes the main characteristics of the trade arrangements signed between countries of the Hemisphere and explores the development of trade rules in these arrangements. Finally, the report details recent advances in the construction of the FTAA.